Long-term trends in airborne SO2 in an air quality monitoring station in Seoul, Korea, from 1987 to 2013. (3rd August 2017) - Khan, Azmatullah; Kim, Ki-Hyun; Szulejko, Jan E.; Brown, Richard J. C.; Jeon, Eui-Chan; Oh, Jong-Min; Shin, Yong Soon; Adelodun, Adedeji A.
ABSTRACT: Atmospheric concentration of sulfur dioxide (SO2 ) was intermittently measured at an air quality monitoring (AQM) station in the Yong-san district of Seoul, Korea, between 1987 and 2013. The SO2 level was compared with other important pollutants concurrently measured, including methane (CH4 ), carbon monoxide (CO), nitric oxide (NO), nitrogen dioxide (NO2 ), ozone (O3 ), and particulate matter (PM10 ). If split into three different periods (period 1, 1987–1988, period 2, 1999–2000, and period 3, 2004–2013), the respective mean [SO2 ] values (6.57 ± 4.29, 6.30 ± 2.44, and 5.29 ± 0.63 ppb) showed a slight reduction across the entire study period. The concentrations of SO2 are found to be strongly correlated with other pollutants such as CO ( r = 0.614, p = 0.02), which tracked reductions in reported emissions due to tighter emissions standards enacted by the South Korean government. There was also a clear seasonal trend in the SO2 level, especially in periods 2 and 3, reflecting the combined effects of domestic heating by coal briquettes and meteorological conditions. Although only a 16% concentration reduction was achieved during the 27-year study duration, this is significant if one considers rapid urbanization, an 83.2% increase in population, and rapid industrialization that took place during that period. Implications : Since 1970, a network of air quality monitoring (AQM) stations has been operated by the Korean Ministry of Environment (KMOE) for routine nationwide monitoring of air pollutant concentrations in urban/suburban areas. To date, the information obtained from these stations has provided a platform for analyzing long-term trends of major pollutant species. In this study, we examined the long-term trends of SO2 levels and relevant environmental parameters monitored continuously in the Yong-san district of Seoul between 1987 and 2013. The data were analyzed over various time scales (i.e., monthly, seasonal, and annual intervals). The results obtained from this study will allow us to assess the effectiveness of abatement strategy and to predict future concentrations trends in association with future abatement strategies and technologies.